Decentralized matching markets with(out) frictions : a laboratory experiment - Pais, Joana (2018)
In a series of laboratory experiments, we explore the impact of different market features (the level of information, search costs, and the level of commitment) on agents’ behaviour and on the outcome of decentralized matching markets. In our experiments, subjects on each side of the market actively search for a partner, make proposals, and are free to accept or reject any proposal received at any time throughout the game. Our results suggest that a low information level boosts market activity but does not affect stability or efficiency of the final outcome, unless coupled with search costs. Search costs have a significant negative impact on market activity, and on both stability and efficiency. Finally, commitment harms stability slightly but acts as a disciplinary device to market activity and is associated with higher efficiency levels of the final outcome.